Chemical tests for identification and characterization of tomato cultivars - Vishwanath, K.; Pallavi, H. M.; Nethra, N.; Rajendra Prasad, S. (Plant Breeding and Seed Science, 2013)
Various chemical tests are being used to reveal chemical differences among the seeds or seedlings of different cultivars. Study to characterize and identify 24 tomato cultivars based on chemical test chemicals viz., Standard phenol test, Modified phenol test, NaOH test, KOH test and Seedling growth response to added chemicals reveled that, most of the cultivars studied were distinct from other cultivars. No single chemical test could distinguish all the varieties. However, distinguishable chemical characteristics were used to develop the keys for identification of each and every cultivar and all the cultivars were distinguished based on these identification